GOVERNMENT EXPENDITURE EFFICACY AND THE QUESTION OF GROWTH: EVIDENCE FROM NIGERIA - Fatai, Ogunlana Olarewaju (European Scientific Journal, ESJ, 2015)
This study analyzes the causal relationship between government expenditure and economic growth in Nigeria. Using the annual time series data for the period 1981 to 2013, the study used cointegration technique and error correction model to ascertain the long run and short run relationship between government expenditure and economic growth. The study further proceeded by conducting Granger causality test. Findings from this study produced mixed results. In the long run, government expenditure was found to influence economic growth negatively while gross fixed capital formation affected growth positively. However, the short run estimate showed that the coefficients of government expenditure and gross fixed capital formation positively influenced economic growth. The granger causality test did not give expected direction of causality between government expenditure and economic growth. Causality test offers little or no support for Wagner’s Law in Nigeria. This study therefore recommends that government expenditure be directed to growth enhancing projects rather than growth retarding ones.